Rituximab in ANCA-associated vasculitis presenting with severe acute kidney injury; a case report - Macaulay Onuigbo; Julius Seok; Ikenna Anyamene; Fortunate Ejimone; Chinenye Eze-Raphael; In-Ah Vanessa Park (Society of Diabetic Nephropathy Prevention, 2019)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis presenting with severe acute kidney injury (AKI), consistent with rapidly progressive glomerulonephritis portends significant renal morbidity with up to 20%-25% of patients reaching end stage renal disease within a few years after diagnosis. Nevertheless, a smaller proportion of patients require dialysis at presentation or within the first six months. There is still some debate as to the first line therapy of choice for such patients vis a vis the use of the newer agent rituximab versus the time-tested cyclophosphamide in combination with glucocorticoids. Our recent experience at The Robert Larner, M.D. College of Medicine, University of Vermont, Burlington, VT, USA in June 2018 allowed us to revisit this controversy.